Pengembangan Sistem Antrian Permohonan Paspor dengan menerapkan Metode User Centered Design (Studi Kasus: Kantor Imigrasi Kelas I Kota Malang) - Amelia Achsandini Puteri; Adam Hendra Brata; Wibisono Sukmo Wardhono (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
Indonesian passports work as identification or identity of Indonesian citizens abroad. Therefore Indonesian citizens who wish to visit abroad for tourism, service or diplomatic activities must have a passport. Applications for passport are generally submitted to the nearest Immigration Office / Passport Service Unit through the Online Passport Service application. With this application, the application queue process should be easy to do. But in fact, many complaints against the application found. App ratings indicate that the current app was unhelpful. In addition, there are several requirements for passport applicants that have not yet been applied to the queue application that is currently used. The design and implementation of a website-based passport application queue system is builded using the user centered design method. The user centered design method applied so that the resulting system can be more accepted and easier to use by passport applicants because system users have diverse demographic backgrounds. By applying the UCD method to the passport application queue system, the usability value is quite high (good). The average value generated by the PSSUQ questionnaire method obtained a value of 1.03 for the System usefulness criteria, 1.28 for the Information quality criteria, 1.40 for the Interface quality criteria and 1.20 for the Overall satisfaction category. The PSSUQ questionnaire has the principle that the smaller the value (closer to 1), the higher the usability value, so it can be concluded that this system is acceptable and easy to use by users.